Comparative Simulation and Modeling of Hydrogen Explosion Consequences Based on TNT Equivalent - Virda Nur Lu'lu; Hary Devianto; Pramujo Widiatmoko (Reaktor, 2026)
Hydrogen is increasingly adopted as a low-carbon energy carrier, creating a need for rapid and auditable blast-consequence screening to inform hazard zoning. This study develops a web-based simulation platform that automates a transparent TNT-equivalent workflow from minimal inputs (inventory volume and evaluation distance). The platform converts volume to mass, estimates TNT-equivalent charge using an energy basis and efficiency factor, applies Hopkinson–Cranz cube-root scaling, and predicts peak side-on overpressure using three well-established empirical correlations (Crowl and Louvar, Alonso, and Sadovski) under harmonized assumptions, while exporting calculation logs for traceability. Validation uses a Type-IV high-pressure hydrogen vessel-burst dataset with measurements at 2–18 m. Over the sensor-intact 6–18 m window, the Alonso correlation achieves MAE 6.006 kPa with R² 0.999, whereas Crowl and Louvar and Sadovski correlations yield MAEs of 18.136 kPa and 17.164 kPa with R² of 0.985 and 0.993. A 50 kg TNT-equivalent Gangneung 2019 case gives 50.9–86.7 kPa at 15 m and 3.58–6.34 kPa at 100 m, consistent with reported steel deformation and widespread glazing damage. Overall, the platform enables transparent, traceable preliminary consequence estimation to support hazard-zoning decisions for hydrogen storage.